For the University Democracy and the Future of the Institution - Docherty, Thomas (Bloomsbury Academic, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. For the University is a book both about and for the university in an age of mass and globalized education. Thomas Docherty analyses the current problems facing the university as an institution, and also offers some positive arguments for a revived and vibrant set of institutional arrangements and governing principles. The book considers the place of the university as an important global institution, now in a charged political and international public sphere. Docherty places current debates within their wider economic and political context, focusing on the relationship of the university to current and emerging models of democracy. The question of what the university will be -- rather than it is, was, or might be -- is at the heart of this book, and Docherty ably traces its history and present condition in order to offer us a vision for the future.